Warfarin Versus Warfarin and Dipyridamole on the Incidence of Arterial Throms Embolism in Prosthetic Heart Valve Patients - Rajah, S.M.; Sreeharan, N.; Rao, S.; Watson, D.A. (Thrombosis and Haemostasis, 1979)
The effect of Warfarin (W) was compared with a combination of Warfarin and Dipyridamole (W+D) on the incidence of arterial thrombo-embolism in patients with prosthetic heart valves in a prospective randomised study. Sixty-four and 53 patients were allocated to W and W+D. The two groups were comparable as regards age, sex, arrhythmias and site and type of valves. The dose of W was determined by regular monitoring of prothrombin ratio 0.9 - 3) and that of D by monitoring serum D levels to between 2 and 4 μmol/l. The mean period of follow-up was 26.98 months (range 1 to 36) for W and 22.02 months (range 1 to 36) for W+D. Six patients in W and 1 in W+D developed arterial thrombo-embolic episodes giving an incidence of 0.0035 per patient month for W and 0.0009 per patient month for W+D. An actuarial analysis of the yearly incidence of thrombo-embolism confirmed the superiority of W+D over W. Of the 6 failures in W, 5 were in sinus rhythm and 1 in atrial fibrillation and all had cerebral embolic episodes. The failure in W+D was a patient in atrial fibrillation who died suddenly 6 weeks after surgery and the post-mortem showed clots on both mitral and aortic prostheses.